Make America gracious again: Collective nostalgia can increase and decrease support for right‐wing populist rhetoric. (1st May 2020) - Lammers, Joris; Baldwin, Matthew
Abstract: Democracies across the globe are shaken by a new class of populist right‐wing politicians. A defining element of right‐wing populism is a preference for antagonistic rhetoric to describe opponents. Three studies connect support for right‐wing populist rhetoric to collective nostalgia for the past. Importantly, the results show that collective nostalgia can both increase and decrease support for right‐wing populist antagonistic rhetoric, depending on how the past is conceptualized. Nostalgia for a past characterized by political incorrectness is associated with increased support, whereas nostalgia for the past's greater decorum is associated with decreased support for right‐wing populism. Studies 1 and 2 show this with vignettes. Study 3 measures support for Trump and the GOP in the 2018 midterm elections. Although right‐wing populism is often seen as the result of a wave of nostalgia, our results show that this link can be disconnected and even reversed.